2020
DOI: 10.1016/j.csbj.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the mechanism of RNA recognition by the N-terminal RNA-binding domain of the SARS-CoV-2 nucleocapsid phosphoprotein

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 45 publications
9
82
0
Order By: Relevance
“…S3, Table S3 ) and highlights, as previously reported (16), a group of cellular kinases associated with N protein. The viral nucleocapsid has been shown to be phosphorylated and phosphorylation is suggested to be important for its function (19, 20). This highlights cellular kinase inhibitors as drugs with possible activity against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…S3, Table S3 ) and highlights, as previously reported (16), a group of cellular kinases associated with N protein. The viral nucleocapsid has been shown to be phosphorylated and phosphorylation is suggested to be important for its function (19, 20). This highlights cellular kinase inhibitors as drugs with possible activity against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…The N protein is highly abundant in the viruses. Its function involves entering the host cells, binding to the viral RNA genome and forms the ribonucleoprotein core to facilitate its replication and process the virus particle assembly and release 27 . Previous reports showed that the N protein from SARS-CoV and MERS-CoV were highly inflammatory nature to promote the expression of inflammatory cytokines, chemokines, prothrombinase and were able to induce acute lung inflammation in mouse model [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus N protein is an important viral structural protein, which plays an important role in promoting of genome packaging, RNA chaperoning, intracellular protein transport, DNA degradation, interference in host translation, and restricting host immune responses [ 8 ]. It is reported that coronavirus N protein may help tether the genome to replicase-transcriptase complex (RTC), and package the encapsidated genome into virions by binding nsp3 protein which is also an antagonist of interferon and viral encoded repressor (VSR) of RNA interference (RNAi) that further benefits the viral replication [ 9 ].…”
Section: Introductionmentioning
confidence: 99%